Genetics, genomics and breeding of fennel - Gabriele Magon; Fabio Palumbo; Gianni Barcaccia (BMC Plant Biology)
Abstract Fennel (Foeniculum vulgare Mill. or Anethum foeniculum) stands out as a versatile herb whose cultivation spans across various regions worldwide, thanks to its adaptability to diverse climatic conditions. Its economic importance is mainly due to its numerous pharmaceutical properties and its widespread use in culinary applications. In this review, we first reviewed the chemical composition of this species, stressing the importance of two volatile compounds: t-anethole and estragole. The few cytological and genetic information available in the scientific literature were summarized. Regarding this latter aspect, we pointed out the almost complete absence of classical genetic studies, the lack of a chromosome-level reference genome, and the shortage of adequate transcriptomic studies. We also reviewed the main agronomic practices, with particular emphasis on breeding schemes aimed at the production of F1 hybrids and synthetic varieties. The few available studies on biotic and abiotic stresses were discussed too. Subsequently, we summarized the main studies on genetic diversity conducted in fennel and the available germplasm collections. Finally, we outlined an overview of the main in vitro regeneration techniques successfully applied in this species.